Application of Interactive Training in Studying Economic Disciplines - S. O. Musienko (Высшее образование в России)
The need for applying interactive teaching methods is dictated by the current legislation of the Russian Federation. It is widely known in the academic  world that active and interactive teaching methods are more effective. They  increase students’ motivation to study, as well as the learning efficiency and  quality. The article describes the characteristics of interactive learning, as  well as the possibility of its application to the study of economic disciplines.  The emphasis is placed on the methodology for implementing interactive  forms of learning relating to theoretical questions, which, unlike the  consideration of practical aspects, remains insufficiently covered. An example of conducting classes in an  interactive form is presented. The presented form of interactive training allows  studying of the majority of economic phenomena, concepts, categories.